"City" and "Population" - considerations on a complex relationship (Revista de História Regional, 2007)
This article attempts to develop a reflection about the various perspectives that have been considered in the relationship between City and Population. In the first moment the discussion concerns the understanding of the relativity and historicity of the thresholds of demographic density that could be characteristic of the City as an specific form of social organization. After this, various aspects are discussed, including the possibilities of speaking in terms of a general characteriology of the urban man